2018
DOI: 10.1038/s41395-018-0097-5
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Dose Threshold for the Chemopreventive Effect of Aspirin Against Gastric Cancer

Abstract: Long-term aspirin use was associated with reduced gastric cancer incidence in the general population of South Korea when the cumulative dose was >3 DDD-years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…Regarding GC, the evidence on the role of aspirin on prevention has been more limited and there is no current recommendation as a chemopreventive agent. Consistent with previous evidence, however, a recent meta-analysis (Huang et al 2017) and a longitudinal study covering the whole population of South Korea concluded that long-term aspirin use was associated with reduction in GC risk (Kim et al 2018). In this high GC risk population, the protective effect was significant in those individuals with cumulative aspirin daily dose use for at least three years.…”
Section: Anti-cancer Strategies Targeting the Pro-inflammatory Mediatsupporting
confidence: 57%
See 2 more Smart Citations
“…Regarding GC, the evidence on the role of aspirin on prevention has been more limited and there is no current recommendation as a chemopreventive agent. Consistent with previous evidence, however, a recent meta-analysis (Huang et al 2017) and a longitudinal study covering the whole population of South Korea concluded that long-term aspirin use was associated with reduction in GC risk (Kim et al 2018). In this high GC risk population, the protective effect was significant in those individuals with cumulative aspirin daily dose use for at least three years.…”
Section: Anti-cancer Strategies Targeting the Pro-inflammatory Mediatsupporting
confidence: 57%
“…Although most cancer research has focused on the molecular changes of the neoplastic cells, it is now recognized that non-tumoral cells in the tumor microenvironment, especially immune cells, proliferate with the tumor and provide essential support for its growth and invasion. The recognized protective effect of non-steroidal anti-inflammatory drugs against GC and other gastrointestinal tumors (Abnet et al 2009; Epplein et al 2008; Kim et al 2018) supports the role of chronic inflammation in carcinogenesis.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Rates of aspirin, metformin, and statins use have increased over the past decades 23 25 , but non-adherence to these medications is also common 26 28 . To clarify the chemoprotective effect of medication, cumulative medication exposure should be taken into account 29 . Second, another important aspect to be considered is the simultaneous use of medications.…”
Section: Introductionmentioning
confidence: 99%
“…These results have prompted the initiation of randomized clinical trials assessing aspirin as a novel adjuvant treatment to surgery in patients with certain cancer types. Regarding gastric adenocarcinoma specifically, observational studies have indicated that aspirin may reduce its incidence [11][12][13], but there is a paucity of data regarding a potential survival benefit of aspirin as an adjuvant therapy to gastrectomy in patients with this cancer.…”
Section: Introductionmentioning
confidence: 99%